ORGANIC AGRICULTURE: SUSTAINABLE AGRICULTURE SOLUTIONS IN PROVIDING FOOD FOR THE COMMUNITY - Yudi Garnida; Willya Achmad (Jurnal Ekonomi, 2022)
The excessive use of inorganic compounds has negative effects on the land and vegetation. Alternative agricultural systems that can produce healthy quantities and quality of products in a sustainable manner must be developed. Organic farming is one of the agricultural systems that support this concept. Organic farming is a method of agriculture that excludes the use of environmentally damaging synthetic pesticides, chemical fertilizers, and cultivation techniques. This research employs a qualitative methodology based on descriptive analysis. The findings of the study indicate that organic farming is a promising strategy for attaining a sustainable food supply through agriculture. By prioritizing the use of renewable resources, reducing the use of non-renewable resources, and avoiding the use of synthetic chemicals, organic agriculture is able to maintain environmental balance, increase the quality and quantity of production, and provide safe and healthy food for consumers. The conclusion of this research will underline the importance of organic farming in providing healthy, safe and quality food for the community. In addition, this research will highlight the benefits of organic farming in maintaining environmental sustainability, such as increasing soil fertility, maintaining biodiversity, and reducing negative impacts on ecosystems.